What is a Cultural Video Game? Study of Teachers’ Perspectives on Cultural Video Games Through the CUDAEVC Questionnaire - Cerezo-Pizarro, Mario; Revuelta-Domínguez, Francisco Ignacio; Guerra-Antequera, Jorge (Journal of Education Culture and Society, 2026)
Aim. To analyse teachers’ perceptions, practices, training needs and perceived barriers regarding the educational use of cultural video games, with the aim of contributing to the operational definition of this concept in educational contexts. Methods. The CUDAEVC questionnaire was administered to 410 teachers across educational levels using non-probability convenience sampling. The ad hoc instrument, validated through expert judgement, addressed three dimensions: the relationship between video game use and cultural acquisition, the conceptualisation of “cultural video game”, and training needs. Results. Only 15% of teachers reported using video games regularly, although 88% perceived a strong link between their teaching practice and ICT. Based on participants’ responses, an operational definition of “cultural video game” is proposed, and key barriers are identified: lack of specific training, limited resources, and difficulty identifying suitable titles. Conclusions. Despite their educational potential, cultural video games remain underused in classrooms and require stronger institutional support. The study acknowledges the limitations of its exploratory design and suggests avenues for future research. Cognitive value. The study addresses an emerging area by examining teachers’ perspectives and proposing an initial definition of “cultural video game” based on a large sample across educational levels. In doing so, it provides both a conceptual and empirical framework for understanding how teachers connect video games with culture and learning, while also identifying key constraints affecting their pedagogical use, particularly limited training, scarce resources, and difficulties in selecting appropriate titles.